Letter - Paterson, J.
026-0083-001 TELEPHONE : MACaulay 2291 (4 LINES) TELEGRAMS: "POSTACT, CLAPCOM, LONDON" UNION OF POST OFFICE WORKERS General Secretary— T. J. Hodgson Asst. Gen Secretary— J. Paterson Asst. Secretary (Outdoor)— H. W. Wallace Asst. Secretary (Indoor)— John Coyne, J.P. U.P.W House, Crescent Lane, Clapham Common, LONDON, S.W.4 Women Organiser & Asst Secretary (Telephones)- Marjorie Peake Organising Secretary— Horace Nobbs General Treasurer— W. T. Leicester Editor— Francis Andrew, Our Ref. G.IN/39 Your Ref. T J.T. Encl 2nd June, 1939. The Secretary, International Solidarity Fund, Transport House, Smith Square, S.W.1. Dear Sir, The Union has recently received an appeal on behalf of certain Trade Unionists who are refugees in France following the defeat of the Spanish Republican Army. The appeal asked for funds to enable parties of Trade Unionists with their families to emigrate to Mexico. You will appreciate that the Union does not desire to duplicate its efforts in this direction, and I should be glad therefore, if you would let me know what steps the International Solidarity Fund are taking in this connexion. Yours sincerely, J. Paterson. Acting General Secretary. 292/946/26/83